2018
DOI: 10.3390/min8120582
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Limit the Adverse Effect of Fine Serpentine on the Flotation of Pyrite

Abstract: A novel method to limit the adverse effect of fine serpentine on the flotation of pyrite was investigated in this paper. The flotation results showed that coarser serpentine possessed a weaker depression effect on the pyrite flotation process, and the use of KAl(SO 4 ) 2 ·12H 2 O could efficiently limit the detrimental effect of fine serpentine on pyrite with a maximum increase of pyrite recovery from 14% to 86% at pH 9.0. The results of particle size measurements and rheological measurements exhibited that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In particular, it was demonstrated that smaller sulfide mineral particles are more oxidized and attract more ferric hydroxides after the comminution in steel mills than coarser ones [192]. The grinding of sulfide ores was found to produce ultrafines in quantities comparable with, or exceeding the amounts of flotation reagents [193,194], particularly serpentine gangues [194][195][196] which bear positive charge and adhere to negatively-charged sulfide minerals, suppressing their flotation. Thus, correct procedures of sampling and handling of mineral dispersions for XPS exploration still need to be elaborated.…”
Section: Sampling and Exploring Natural Mineral Dispersionsmentioning
confidence: 99%
“…In particular, it was demonstrated that smaller sulfide mineral particles are more oxidized and attract more ferric hydroxides after the comminution in steel mills than coarser ones [192]. The grinding of sulfide ores was found to produce ultrafines in quantities comparable with, or exceeding the amounts of flotation reagents [193,194], particularly serpentine gangues [194][195][196] which bear positive charge and adhere to negatively-charged sulfide minerals, suppressing their flotation. Thus, correct procedures of sampling and handling of mineral dispersions for XPS exploration still need to be elaborated.…”
Section: Sampling and Exploring Natural Mineral Dispersionsmentioning
confidence: 99%